Leadership for sustainability an action research approach - Marshall, Judi.; Coleman, Gill, 1954-; Reason, Peter; ProQuest (Firm) (Sheffield, U.K. : Greenleaf, 2011)
This book focuses on what it means to take up leadership for sustainability, from a variety of organisational and social positions, and considers the consequences of different strategies and practices for influencing change. Whatever form it takes, organisational sustainability programmes need committed, intelligent, reflective leadership at all levels to make them work. The examples in this book show how people in very different contexts have seized the opportunities open to them and acted with courage and initiative to make a difference. This book will be relevant to a wide range of people, including managers, consultants, and others in commercial, non-profit, public and intergovernmental organisations who want to contribute to the development of a sustainable world. It will be of particular interest to people working in organisations already thinking about issues of sustainability and those who are seeking to take on the role of change agents in organizations or communities. -- taken from back cover.
ch. 1. Taking up the challenge -- ch. 2. Educating for inquiring practice in sustainability -- ch. 3. Ideas and practices -- ch. 4. Promoting alternative questioning, policies and practices in mainstream organisations -- ch. 5. Establishing sustainability practices in organisations and industries -- ch. 6. Paying attention to everyday practices of sustainable living -- ch. 7. Seeking to shift systemic rules and awareness -- ch. 8. Connecting up stakeholders for more sustainable outcomes -- ch. 9. Itinerant change agents to professions and sectors -- ch. 10. Working through community and society -- ch. 11. Working with young people -- ch. 12. Reflections.
Includes bibliographical references (p. [238]-247) and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Social responsibility of business; Associations, institutions, etc. -- Environmental aspects; Corporations -- Environmental aspects; Industries -- Environmental aspects; Sustainability; Leadership; Electronic books